A novel naphthalenediimide-based lanthanide–organic framework with polyoxometalate templates exhibiting reversible photochromism. Issue 15 (20th March 2017) - Zhang, Hai-Long; Liao, Jian-Zhen; Yang, Wenbin; Wu, Xiao-Yuan; Lu, Can-Zhong
Abstract : The first visible-light-responsive photochromic polyoxometalate-templated lanthanide–organic framework (LOF) has been constructed from a carboxyphenyl-substituted naphthalenediimide (NDI) derivative. Abstract : The first visible-light-responsive photochromic polyoxometalate-templated lanthanide–organic framework (LOF) has been constructed from a carboxyphenyl-substituted naphthalenediimide (NDI) derivative, which displays an unusual four-fold interpenetration of an srs topological network, featuring a variety of anion–π interactions between polyoxoanions and π-acidic NDI moieties, and undergoes a rapid reversible photochromic transformation upon blue light irradiation.